Design, validation, and effectiveness of a Jambi local wisdom-based interactive worksheet for enhancing preschool children's numeracy skills - Anniska Nuria; Setiyo Utoyo; Delfi Eliza; Nenny Mahyuddin (CV. FOUNDAE, 2026)
Background: Developing numeracy skills during early childhood is essential for establishing a strong foundation for later mathematical learning. However, limited availability of interactive learning materials that integrate local cultural contexts has reduced opportunities for meaningful and engaging numeracy experiences. Aim: This study aimed to design, validate, and evaluate the effectiveness of a Jambi local wisdom-based interactive worksheet for enhancing the numeracy skills of preschool children aged 5–6 years. Method: A Research and Development approach employing the ADDIE model was adopted. The study involved 27 preschool children, including 12 participants in a small-group trial and 15 in a large-group implementation. The developed worksheet was evaluated through expert validation, practicality assessment, and effectiveness testing using a one-group pretest–posttest design. Data were analyzed using descriptive statistics, the Wilcoxon Signed-Rank Test, and normalized gain (N-Gain). Results: The worksheet achieved excellent validity, with expert validation scores of 91.6%, 100%, and 94.2% for media, content, and numeracy assessment, respectively. It was also rated highly practical (95%). Statistical analysis revealed a significant improvement in children's numeracy skills (p = 0.001), with a high average N-Gain score of 0.8545 (85.4%). Conclusion: The Jambi local wisdom-based interactive worksheet is valid, practical, and highly effective in improving preschool children's numeracy skills while promoting contextual and culturally meaningful mathematics learning.